Late Pliocene–early Pleistocene deep‐sea basin sedimentation at high‐latitudes: mega‐scale submarine slides of the north‐western Barents Sea margin prior to the shelf‐edge glaciations. (20th November 2015) - Safronova, P. A.; Laberg, J. S.; Andreassen, K.; Shlykova, V.; Vorren, T. O.; Chernikov, S.
Abstract: At high‐latitude continental margins, large‐scale submarine sliding has been an important process for deep‐sea sediment transfer during glacial and interglacial periods. Little is, however, known about the importance of this process prior to the arrival of the ice sheet on the continental shelf. Based on new two‐dimensional seismic data from the NW Barents Sea continental margin, this study documents the presence of thick and regionally extensive submarine slides formed between 2.7 and 2.1 Ma, before shelf‐edge glaciation. The largest submarine slide, located in the northern part of the Storfjorden Trough Mouth Fan (TMF), left a scar and is characterized by an at least 870‐m‐thick interval of chaotic to reflection‐free seismic facies interpreted as debrites. The full extent of this slide debrite 1 is yet unknown but it has a mapped areal distribution of at least 10.7 × 10 3 km 2 and it involved >4.1 × 10 3 km 3 of sediments. It remobilized a larger sediment volume than one of the largest exposed submarine slides in the world – the Storegga Slide in the Norwegian Sea. In the southern part of the Storfjorden TMF and along the Kveithola TMF, the seismic data reveal at least four large‐scale slide debrites, characterized by seismic facies similar to the slide debrite 1. Each of them is ca . 295‐m thick, covers an area of at least 7.04 × 10 3 km 2 and involved 1.1 × 10 3 km 3 of sediments. These five submarine slide debrites represent approximately one quarter of the total volume of sediments deposited during the time 2.7–1.5 Ma along the NW Barents Sea. The preconditioning factors for submarine sliding in this area probably included deposition at high sedimentation rate, some of which may have occurred in periods of low eustatic sea‐level. Intervals of weak contouritic sediments might also have contributed to the instability of part of the slope succession as these deposits are known from other parts of the Norwegian margin and elsewhere to have the potential to act as weak layers. Triggering was probably caused by seismicity associated with the nearby and active Knipovich spreading ridge and/or the old tectonic lineaments within the Spitsbergen Shear Zone. This seismicity is inferred to be the main influence of the large‐scale sliding in this area as this and previous studies have documented that sliding have occurred independently of climatic variations, i.e. both before and during the period of ice sheets repeatedly covering the continental shelf.